Project-Based Learning for Developing Sociolinguistic Competence among University Students in Japanese Language Education: Pembelajaran Berbasis Proyek untuk Mengembangkan Kompetensi Sosiolinguistik di Kalangan Mahasiswa Program Pendidikan Bahasa Jepang - Amelya Septiana (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
This study describes the implementation of project-based learning (PBL) in a Sociolinguistics course for undergraduate students of Japanese language education. Through individual projects, students were tasked with developing small-scale research papers on sociolinguistic issues in Japanese, bridging theoretical knowledge with authentic academic practice. The study employed a qualitative classroom re-search design involving 70 undergraduate students in a Japanese language education program. Data were collected through students’ project reports, reflective journals, and instructor observations, and ana-lyzed using thematic analysis to examine the development of sociolinguistic competence, The data were collected from students’ project reports, reflective journals, and instructor observations. Findings indicate improved performance-based outcomes, particularly in students’ ability to apply sociolinguistic concepts in research writing, use appropriate registers, and analyze politeness strategies in context. Qualitative themes highlighted increased sociolinguistic awareness and deeper connections between language, cul-ture, and context. The paper argues that PBL provides a viable framework for cultivating higher-order thinking skills, learner autonomy, and intercultural sensitivity in Japanese language education. Implica-tions are offered for curriculum design, teacher training, and future research on linking linguistic theory with practical applications in foreign language classrooms.